A liturgical comparative study of Sotho initiation and Christian baptism - Rantoa Letšosa; Ben de Klerk (In die Skriflig, 2019)
At first glance, there appears to be similarities between traditional Sotho initiation and Christian baptism, as both give the individual entrance into a new stage of life. This study compares African initiation in the Sotho context with initiation and baptism in the Christian context. The following aspects served as comparison: concepts of initiation, admission requirements, separation and new naming, the process of initiation through circumcision and baptism, community and the initiation, teaching in the initiation, and controversies in the initiation process. The correct biblical teaching and the right approach will overcome wrong teachings that emanate from African concepts about ancestral spirits and witchcraft, and the initiation school. This comparison opens the eyes for the Sotho initiation to discover and rethink the importance of the concept of baptism, the requirement of faith in baptism, the radical separation of the baptised person from the unbaptised, the importance of new naming, the Name of the triune God, the beauty of the process of baptism, the importance for the baptised to live, to experience and contribute to the community life of the church, the necessary teaching before and after baptism and to deal with controversies on the basis of Scripture.